Characterizing the Ectomycorrhizal Fungal Community of Whitebark Pine in Interior British Columbia: Mature Trees, Natural Regeneration and Planted Seedlings - Southam, Hanno; Stafl, Natalie; Guichon, Shannon H. A.; Simard, Suzanne W. (Frontiers in Forests and Global Change, 2022)
Whitebark pine (Pinus albicaulis Engelm.; WBP) is an endangered subalpine tree species and requires associations with ectomycorrhizal fungi (ECMF) for survival and growth. Despite this obligate dependence, there are gaps in the identification of ECMF that associate with WBP. In addition, ECMF rarely feature in assessments of recovery actions and little is known about the relationship between ECMF and the insects and pathogens affecting WBP. We used next-generation sequencing to characterize ECMF occurring in soil and mycorrhizal root tip samples from naturally occurring mature WBP trees and seedlings as well as planted WBP seedlings in the Columbia Mountains of Interior British Columbia, Canada. ECMF data was paired with data on tree age, tree health and soil conditions. Thirty-three species and twenty-one genera of ECMF were identified with medium or high confidence from mycorrhizal root tip samples. Major groups were: generalist ascomycetes [Cenococcum, Meliniomyces (=Hyaloscypha)], Atheliales (Piloderma, Amphinema, Tylospora), non-ascomycetous generalists (e.g., Amphinema), associates of high-elevation conifers (species of Cortinarius, Russula) and Suilloids (Suillus, Rhizopogon). Differences in WBP ECMF with other, drier and southerly regions that have been studied previously, were consistent with a distinct forest type and an endemism hypothesis. Soil at the planting site and planted seedlings hosted a reduced ECMF community or were non-ectomycorrhizal, which can be explained by site factors and is expected to affect seedling survival. ECMF composition on mature trees was correlated with tree health, which may have implications for WBPs resistance to pathogens and signals that ECMF are affected by the decline of their host. Understanding the ecology of WBP ECMF and their relationship with tree performance is essential for WBP recovery efforts.